Intelligent Walking Aid (IWA) for Elderly - Yousri, Nur'Afifah; Wan Mahmud, Wan Mahani Hafizah (Evolution in Electrical and Electronic Engineering, 2022)
Walking frame (WF) is one of the walking aids that the elderly use to move from one place to another place. When using a WF on a rough surface, the WF is hard to move because of the smaller width of the wheels. The main objective of this project is to develop hardware for the elderly to move using intelligent walking aid (IWA) on a rough and smooth surface. This project introduces the steel, WF, chair and hoverboard as hardware parts that will attach together while 3D SOLIDWORK software is in the designing stage. The result shows that IWA is functioning well on both surfaces and it shows that on the smooth surface, IWA is more stable and more speed which only takes 10.94s on the smooth surface while on the rough surface it takes 50.93s to finish 15-meter length. By upgrading the standard WF to technology, it can help the elderly to move without tiring and users can be more stable than using a standard WF.